3D FEM Simulation For Fully Grouted Bolts - Khaled Morsy (International Conference on Ground Control in Mining, 2004)
Most of the available numerical codes simulating the reinforcing effect of fully grouted bolt are accomplished by a series of bar elements which are connected along their length to the host rock by shear springs and sliders. The spring-slider system represents the shear bonding effect between the bolt and the host rock. This paper describes a three dimensional finite element modeling technique for the 3D simulation of fully grouted bolt reinforcement. The proposed technique introduced a physical simulation for the fully grouted bolts. The bolt simulation is composed of a series of beam elements (representing the steel rebar) embedded in brick elements (representing the grout). Because of the complexity of the grout/rock interface, ABAQUS explicit code was used. A modification of the ABAQUS default friction model was conducted to consider the cohesion of the grout/rock interface. The interaction between the grout and the host rock is simulated by the modified friction model. To verify the proposed technique, a simulation of the pull out test we conducted. The results from the simulation were compared with former studies